PENGARUH METODE PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) DAN KONVENSIONAL TERHADAP HASIL BELAJAR SISWA KELAS VII PADA PELAJARAN PKN MTS NURUL KAROMAH KECAMATAN GALIS KABUPATEN BANGKALAN - Nurul Maulida; Sunardjo; Anindita Trinura Novitasari (Penerbit STKIP PGRI Bangkalan, 2019)
Civic education is a subject that focuses on forming good citizens in the life of society, nation and state. Learning Civic Education is learning by empowering students to become useful human beings, able to compete and can provide great benefits for life and the environment. The use of Contextual Teaching and Learning (CTL) as learning method makes students enthusiastic in conducting question and answer, expressing their opinions and giving advice to other students by linking the theory they learn. The method in this study was a quantitative method. In addition, the design used was a quasi-experimental study using two variables to determine the effect of the Contextual Teaching and Learning (CTL) method and the conventional method of the results. Based on the conclusions data analysis shows that learning Civic Education with the Contextual Testing and Learning (CTL) method is better than learning with conventional methods. there are differences in student learning outcomes after using the contextual teaching and learning (CTL) method.